Calicinal trichomes of Adenocalymma magnificum (Bignoniaceae) producing lipophilic substances: ultrastructural and functional aspects - Serra Gama, Thália do Socorro (Universidad de Costa Rica, 2015)
Plant structures that secrete lipids and phenolic compounds are often associated with the protection and development of organs against desiccation, in addition to the protection they provide against animals, as the capitate trichomes of Adenocalymma magnificum. Understanding the glandular activities that occur in these trichomes has required the study of their ontogeny, structure, ultrastructure and histochemical aspects; the interpretation of their ecological functions or evolutionary history is complicated by the scarcity of reports on calicinal trichomes that are not nectar-secreting. Samples of floral calyx in anthesis and flower buds at different stages of development were fixed and processed according to the methods for light and electron microscopy. The trichomes are randomly distributed throughout the entire inner surface of the calyx and are also visible on the flower buds. These capitate glandular trichomes were composed of a peduncle, having up to nine cells, and a multicellular secretory head with their cells in columnar format and arranged in disc form. The collar cell, which is under the secretory head, divides anticlinally and arranges itself side by side with the mother cell. As they develop, they bend with some of them becoming adpressed to the calyx. Histochemical tests indicate that the secretory head cells produce lipid substances, acidic lipids and phenolic compounds. In the secretory head, the vacuome is dispersed and the cytoplasm possesses a great number of smooth endoplasmic reticulum and leucoplasts, organelles involved in the production of osmiophilic substances. In some regions of the secretory cells, cuticle detachment was observed; however, the accumulation of secretions was not observed. This study describes, for the first time, the origin, development, and secretion process of the calicinal trichomes of Adenocalymma magnificum, showing that production of lipophilic substances is important for this plant, possibly the trichomes may be involved in the plant’s chemical defense against insects, offering protection against herbivores.